2021
DOI: 10.1038/s41598-020-80280-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals resistant and susceptible genes in tobacco cultivars in response to infection by Phytophthora nicotianae

Abstract: Phytophthora nicotianae is highly pathogenic to Solanaceous crops and is a major problem in tobacco production. The tobacco cultivar Beihart1000-1 (BH) is resistant, whereas the Xiaohuangjin 1025 (XHJ) cultivar is susceptible to infection. Here, BH and XHJ were used as models to identify resistant and susceptible genes using RNA sequencing (RNA-seq). Roots were sampled at 0, 6, 12, 24, and 60 h post infection. In total, 23,753 and 25,187 differentially expressed genes (DEGs) were identified in BH and XHJ, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Transcriptional profiles of several crop plants after pathogen infections clarified particular metabolic and signaling pathways tightly related to compatible and incompatible interaction ( Cregeen et al, 2015 ; Gyetvai et al, 2012 ; Meng et al, 2021 ; Sonah et al, 2016 ; van Esse et al, 2009 ; Wang et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional profiles of several crop plants after pathogen infections clarified particular metabolic and signaling pathways tightly related to compatible and incompatible interaction ( Cregeen et al, 2015 ; Gyetvai et al, 2012 ; Meng et al, 2021 ; Sonah et al, 2016 ; van Esse et al, 2009 ; Wang et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although considerable efforts have been made to understand genetic mechanisms of black rot resistance in Brassica crops ( Islam et al, 2017 , 2019 ; Song et al, 2020 ; Sun et al, 2021 ), key genes underlying variation in black rot resistance are thus far largely unknown. Insights into the transcriptional dynamics of plant-pathogen interactions can help to potentially pinpoint genes underlying pathogen resistance ( Meng et al, 2021 ). To elucidate the transcriptional response of B. napus to black rot infection, we performed comparative transcriptome sequencing of three B. napus lines with different levels of susceptibility at three time points after Xcc inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…The RipAB effector is responsible for the repression of three CMLs, one CDPK, and a Ca 2+ transporter in potato. In 2021, Meng et al [83] reported that among the root genes, specifically, and rapidly upregulated in tobacco-resistant cultivar to Phytophthora nicotianae, four CMLs were identified, whereas the Loc107773369 gene, which corresponds to the closest tobacco ortholog to CML8, was downregulated. CML8 is the closest homolog to the soybean CaM4 and when overexpressed, CaM4 is responsible for enhanced resistance to the oomycete Phytophthora sojae and two necrotrophic fungi, Alternaria tenuissima and Phomopsis longicolla [84].…”
Section: Discussionmentioning
confidence: 99%